STRATEGI DAKWAH NAHDLATUL ULAMA TERHADAP TOLERANSI BERAGAMA DI JEPARA - Miftahul Huda (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
This study aims to find out the strategy of Nahdlatul Ulama da’wah to religious tolerance in Jepara. In this study, the strategy used by Nahdlatul Ulama is based on the theory of change, which means striving for a space for strengthening and accepting local religious and belief groups that receive discrimination, and intolerance through early conflict warning and response systems, strengthening mediation capacity and fulfilling efforts economic empowerment. The form of activities in campaigning for religious tolerance carried out by Nahdlatul Ulama is to use participatory strategies through educational, cultural, mediation, policy advocacy and mentoring approaches to the Women’s Light Mandiri Group. In the program method, Nahdlatul Ulama prioritizes discussion, and collaboration between wisdom and kind preaching (mawi§ah ¥asanah), meaning that it adapts to the conditions of the times and is packed with motivating efforts, aiming to achieve common goals with the methods and approaches used.